Continuous Electrical Oscillations Emerge from a Coupled Network: A Study of the Inferior Olive using Lentiviral Knockdown of Connexin36 - Placantonakis, Dimitris G. (J Neurosci, 2006)
Do continuous subthreshold oscillations in membrane potential within an electrically coupled network depend on gap junctional coupling? For the inferior olive (IO), modeling and developmental studies suggested that the answer is yes, although physiological studies of connexin36 knock-out mice lacking electrical coupling suggested that the answer is no. Here we addressed the question differently by using a lentivirus-based vector to express, in the IO of adult rats, a single amino acid mutation of connexin36 that disrupts the intracellular trafficking of wild-type connexin36 and blocks gap junctional coupling. Confocal microscopy of green fluorescence protein-labeled dendrites revealed that the mutant connexin36 prevented wild-type connexin36 from being expressed in dendritic spines of IO neurons. Intracellular recordings from lentivirally transduced IO networks revealed that robust and continuous subthreshold oscillations require gap junctional coupling of IO neuron somata within 40 μm of one another. Topological studies indicated that the minimal coupled network for supporting such oscillations may be confined to the dendritic arbor of a single IO neuron. Occasionally, genetically uncoupled IO neurons showed transient oscillations; however, these were not sustained longer than 3 s and were 69% slower and 71% smaller than the oscillations of normal IO neurons, a finding replicated with carbenoxolone, a pharmacological antagonist of gap junctions. The experiments provided the first direct evidence that gap junctional coupling between neurons, specifically mediated by connexin36, allows a continuous network oscillation to emerge from a population of weak and episodic single-cell oscillators. The findings are discussed in the context of the importance of gap junctions for cerebellar rhythms involved in movement.